Anak Berbakat (Jenius Atau Gifted Children) - Aat Maratun Sholehah; Khamim zarkasih putro (Universitas Ngudi Waluyo, 2022)
Talent is an ability which is something that is inherent (has existed and is integrated) in a person, carried from birth and related to the structure of the brain. Other factors that play a role on intelligence are nutritional and neurological factors. Gifted children are described as children who have more potential than children of the same age in general. In general, there are two ways to identify gifted children, namely, gathering information in an objective way and gathering information that is subjective in nature. The characteristics of the genius / gifted children, namely children who have a high iq above the average iq in the population, namely> 130. This study aims to present the gifted children (genius or gifted children). This research was conducted by analyzing library research (Library Research). Based on the results of data analysis through literature study obtained from the compilation of data by carrying out a search of books, literature, notes, as well as various relevant information by showing that gifted children (geniuses or gifted children) should know as early as possible.